Pengaruh Penambahan Konsentrasi Air Garam Laut dan Lama Perendaman Terhadap Mutu bunga Kol (brassica oleracea var. Botrytis l.) Selama Penyimpanan Suhu Dingin - Maria Wardiani Popi; Ida Ayu Rina Pratiwi Pudja; I Putu Surya Wirawan (Program Studi Teknik Pertanian dan Biosistem, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2021)
Cauliflower (Brassica oleracea var. botrytis L.) is one of the perishable agricultural products. Handling these problems, preservation is necessary in order to maintain the quality of cauliflower. One technique that can be used for preservation is soaking with salt. The purpose of this study was to determine the effect of salt water concentration and soaking time on the quality of cauliflower during cold storage and to determine the best salt concentration on quality and the best soaking time on cauliflower. This research method uses a Completely Randomized Design (CRD) consisting of 10 treatments and 2 replications with a concentration of salt (NaCl) of 3%, 6%, 9% and soaking time of 10, 20 and 30 minutes. The results showed that soaking using table salt (NaCl) 10 grams with a concentration of 6% and soaking time for 20 minutes showed the best results after 10 days of observation.